2020
DOI: 10.1002/ijfe.1829
|View full text |Cite
|
Sign up to set email alerts
|

Banking sector stability and economic growth in post‐transition European Union countries

Abstract: Economic growth is considered to be an essential means for poverty alleviation and improving countries' well‐being. Disturbances and instability in the banking sector may jeopardize financial stability and generate adverse, considerable and long‐lasting consequences therefor. This study analyzed the dynamic and causal effects of various indicators of banking sector stability on economic growth by employing new generation panel cointegration and causality tests in post‐transition European Union countries over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Institutional quality index examined in our inquiry is unique to this study because it is an author-constructed index using principal component analysis (PCA) process; additionally, some components of this index, which are later examined separately, are different compared to what can be found in the literature. Furthermore, instead of the contributions of the financial sector to economic growth, which dominates the literature (see Adeel-Farooq et al, 2020;Maciejewski and Głodowska, 2020;Bayar et al, 2021), this study rather focuses on financial development and the role of institutions of governances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Institutional quality index examined in our inquiry is unique to this study because it is an author-constructed index using principal component analysis (PCA) process; additionally, some components of this index, which are later examined separately, are different compared to what can be found in the literature. Furthermore, instead of the contributions of the financial sector to economic growth, which dominates the literature (see Adeel-Farooq et al, 2020;Maciejewski and Głodowska, 2020;Bayar et al, 2021), this study rather focuses on financial development and the role of institutions of governances.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, instead of the contributions of the financial sector to economic growth, which dominates the literature (see Adeel-Farooq et al. , 2020; Maciejewski and Głodowska, 2020; Bayar et al. , 2021), this study rather focuses on financial development and the role of institutions of governances.…”
Section: Introductionmentioning
confidence: 99%
“…Khattab et al (2015) for MAGHREB countries, Alsamara et al (2019) for Qatar and Jima and Makoni (2023) for SSA, showed that financial stability plays an important role on encouraging economic growth and vice versa. On the other hand, Boachie et al (2021) and Bayar et al (2021) found only unidirectional causality from economic growth to financial stability.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Excessive credit growth is one of the main factors associated with banking or financial crises in developing countries. Even though an increase in credit can positively contribute to economic growth in the long run, in the short run it might lead to poor credit allocation creating economic imbalance [ 16 ]. Excessive credit growth can lead to financial crises via three channels: the first is by generating external macroeconomic imbalances; second, by inflating asset price resulting in bubbles and busts; third, by leading to inefficient use of resources [ 17 ].…”
Section: Introductionmentioning
confidence: 99%